Peningkatan Keterampilan Menulis Puisi Menggunakan Metode Nature Learning Pada Siswa Kelas VIII-6 SMP Pahlawan Nasional - Amelia Br Barus; Khanaya Shalsabilla; Vera Adzania; Mustika Wati Siregar (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This type of research is Classroom Action Research (PTK). The subjects in this research were in class VIII-6 with a total of 20 students. The aim of this research is to improve the learning quality of students in class VIII-6 of National Hero Middle School in writing poetry using the Nature Learning method. The Nature Learning method is a learning method that uses the natural environment as a medium. Based on research, the application of the Nature Learning method is very effective because students' poetry writing results have increased from cycle I to cycle II.